Clinical Reasoning in Forensic Psychiatry: Concepts, Processes, and Pitfalls - Raharjanti, Natalia Widiasih; Wiguna, Tjhin; Purwadianto, Agus; Soemantri, Diantha; Bardosono, Saptawati; Poerwandari, Elizabeth Kristi; Mahajudin, Marlina S.; Ramadianto, Adhitya Sigit; Alfonso, César A.; Findyartini, Ardi; Nugrahadi, Nadia Rahmadiani; Lazuardi, Muhammad Qolby; et al. (Frontiers in Psychiatry, 2021)
Forensic psychiatrists are often sought by the court of law to provide professional opinion on specific legal matters that have a major impact on the evaluee and possibly society at large. The quality of that opinion and recommendations rely on the quality of the analysis from the assessment results conducted by the psychiatrist. However, the definition and scope of a forensic psychiatric analysis is not clear. While existing literature on forensic psychiatric analysis generally includes organizing information, identifying relevant details, and formulating a set of forensic psychiatric opinions as components, there is no explicit and unified definition of these terms and process. This lack of clarity and guidelines may hinder forensic psychiatry from achieving its goal of providing objective information to the court or other relevant parties. Forensic psychiatric analysis exhibits numerous parallels to clinical reasoning in other fields of medicine. Therefore, this review aims to elaborate forensic psychiatric analysis through the lens of clinical reasoning, which has been developed by incorporating advances in cognitive sciences. We describe forensic psychiatric analysis through three prominent clinical reasoning theories: hypothetico-deductive model, illness script theory, and dual process theory. We expand those theories to elucidate how forensic psychiatrists use clinical reasoning not only to diagnose mental disorders, but also to determine mental capacities as requested by law. Cognitive biases are also described as potential threat to the accuracy of the assessment and analysis. Additionally, situated cognition theory helps elucidate how contextual factors influence risk of errors. Understanding the processes involved in forensic psychiatric analysis and their pitfalls can assist forensic psychiatrists to be aware of and try to mitigate their bias. Debiasing strategies that have been implemented in other fields of medicine to mitigate errors in clinical reasoning can be adapted for forensic psychiatry. This may also shape the training program of general psychiatrists and forensic psychiatrists alike.